Aloe vera–eluting collagen I microgels: physicochemical characterization and in vitro biological performance (2022)
Microgels absorb and retain high amounts of solvents, especially water. Because of their size, and association, the release kinetics of active molecules from microgels is easier to control than in hydrogels. Collagen I is one of the most extensively investigated biomaterials, although the key process parameters to produce microgels must be understood well before they can be used in veterinary and human medicine. Emulsification-gelation is widely used to obtain microgels because of its ease of handling and high yields. The concentration of the biomaterial and the homogenization method are among the critical parameters in this method. In this work, we produced cytocompatible collagen I microgels by emulsification-gelation and evaluated the effect of three different concentrations and homogenization methods on their physicochemical, mechanical, and biological properties. As proof of concept, microgels were loaded with an Aloe vera extract and the loading efficiency and the polyphenol release kinetics, as well as their properties assessed. When the same homogenization method (e.g. magnetic stirring) was used, the size of the microgels decreased with an increase of collagen I concentration, and the size distribution increased. In addition, the size and size distribution of microgels prepared with the same collagen I concentration were smaller when produced by high-energy homogenization methods (shear stress and ultrasound) than with a low-energy one (magnetic stirring). Collagen I concentration and the homogenization method also influenced the zeta-potential, the enzymatic degradation, and the encapsulation efficiency of the microgels. Overall, we show that the size of these microgels can be fine-tuned by the collagen I concentration and the homogenization method. Moreover, the integration of microgels of different sizes into the same carrier platform will pave the way for the combination of active compounds with different release kinetics.